Analisis Gejala Bahasa Dalam Karangan Siswa Kelas V di Sekolah Dasar Negeri 82 Kota Bengkulu - aulia nuur asiyah; sri ken kustianti; abdul muktadir (JURIDIKDAS, 2021)
The study entitled An Analysis of Language Symptoms in student’s essays in fifth grade at Elementary Schools number 82 in Bengkulu City, aims to describe the language symptoms that occur in the essays of fifth grade students at Elementary School number 82 Bengkulu city. This research employed a qualitative descriptive study. The data used in this study were a portfolio of assignments written essay by fifth grade students of Elementary School number 82 Bengkulu City with free topics. The focus of the research studied was the forms of habitual pattern changes (reduction), the addition of phonemes, hypercorrect, and pleonasm. The instrument was used in the form of card data to provide identity to the essays and language symptom analysis tables. The data technique used in this research is document study. The research data collected a portfolio of student assignments written in essays on free topics and in accordance with the applicable curriculum. The research was carried out in 2 stages, namely the first was preparation consisting of data and organizing and grouping the collected data, second was data analysis which consists of data reduction, data retrieval, and conclusions or clarification. The results of this study indicated that in the use of language in the essays of the fifth grade students of Elementary School number 82 Bengkulu City, there are language symptoms in the form of (1) phoneme decline or reduction (apheresis, syncope, apocope), (2) additional phonemes or additions (prosthesis, epenthesis, paragog), (3) hypercorrect, and (pleonasm). This can be seen from several words and sentences found in student’s essays do the language symptoms.